Análise das políticas públicas na ótica de mulheres vítimas de violência psicológica - Gonçalves, Angenilda dos Reis (2024)
Some women victims of domestic violence are convinced of the impunity of the aggressor, while some believe they deserve the treatment they receive from their partners. The present research aimed to analyze the effectiveness of existing public policies in the Federal District that offer support to women victims of psychological violence. This is a qualitative study with an exploratory and descriptive approach. For the analysis of data collected through interviews, the content analysis technique proposed by Bardin was used. The results show that domestic violence does not discriminate based on age, race, religion, or educational level. Victims may not recognize certain behaviors as manifestations of psychological violence, and when they seek help, they feel insecure, fearing not to be treated with due respect and dignity by the public system. The research participants who chose to report their partners expressed feelings of discomfort and inadequacy in the service environment when recounting their traumatic experiences. The majority demonstrate a superficial knowledge of the Maria da Penha Law and express disbelief in the effectiveness of public policies promoted by the State. It was observed through the participants' reports that the psychological violence perpetrated by aggressors is facilitated by deficient and ineffective public policies. It is up to the State to mitigate cases of discrimination against women by adopting legal, programmatic, and public policies aimed at reducing inequalities between men and women. Education is considered a fundamental factor in the prevention and combat of any type of violence. Schools play a fundamental role in promoting a preventive and non-violent culture. Therefore, it is essential to integrate educational programs in educational institutions that address topics such as respect, empathy, gender equality, and violence prevention.